STUDY ON THE CONSUMER ACCEPTANCE TO THE CATFISH (Pangasius hypophthalmus) DIM SUM FORTIFIED BY BLUE-GREEN ALGAE (Spirulina) - Abraham Manik; Dewita Dewita; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to assess the consumer acceptance to the catfish dim sum fortified by spirulina. The research method used was an experimental method by making dim sum with different amounts of spirulina fortified. This study used a completely randomized design with 4 treatments and 3 replications. The treatments were fortification of spirulina (0, 5, 10, 15 gs) to the catfish dim sum. The results showed that the best treatment was the fortification of 5 gs spirulina, indicated by the highest consumers acceptance to dim sum up to 82.09% (66 of 80 panelists) that was evaluated by the hedonic value of appearance, smell, and taste. The best dim sum was characterized by the light green and bright appearance; the smell of catfish and spices was felt, the smell of spirulina was a little fishy; the taste of catfish and seasoning was felt, the taste of spirulina wasa little bitter; chewy texture, a little solid, and a little soft. The proximate values of the dim sum were the content of moisture 51.99%, ash 1.08%, protein 5.65%, and fat 3.69%.Keywords: Dim Sum, Fortification, Spirulina